CVF1 Promotes Invasive Candida albicans Infection via Inducing Ferroptosis - Gang Luo; Yongman Ma; Chunyi Chen; Yudie Hu; Chunchun Yan; Di Wang; Cong Wang; Yanyan Wang; Xichen Yu; Andriy Sibirny; Jun Yuan; Yingqian Kang (Journal of Fungi)
Recent studies have shown that several pathogens manipulate ferroptosis in host cells to aid their dissemination and enhance pathogenicity. While bacterial virulence factors capable of inducing ferroptosis have been identified, no such factors have been reported for human fungal pathogens thus far. Candida albicans, a most common human pathogenic fungus causing invasive fungal diseases, has recently been found to be able to induce ferroptosis in macrophages. Whether specific virulence factors induce ferroptosis in host cells that promote C. albicans pathogenicity remains to be defined. Here, we identify CVF1 as a critical virulence gene of C. albicans that is required for systemic fungal infection. Moreover, the CVF1 gene can significantly promote macrophage death. Using a macrophage infection model combined with the addition of cell death inhibitors, we show that the CVF1-induced death of macrophages is attributed to ferroptosis. More importantly, CVF1 is sufficient to trigger ferroptosis to promote C. albicans dissemination and pathogenicity in vivo. This study highlights a mechanism by which a virulence factor from a human fungal pathogen regulates ferroptosis in host cells, supporting the concept that human pathogenic fungi harbor specific virulence factors to manipulate ferroptosis in host cells for their invasive infection.